Multilateralism, Foreign Policy, and National Interests of States: A case Study of Nigeria - Oladimeji, Talibu (Department of International Relations, Hasanuddin University, 2025)
Great powers within the global system are deemed to be financially and militarily powerful to stand behind the multilateral institutions as sentinel and use such as a tool of achieving national interests. In this case, most researchers have toed such a line of reasoning while sidelining the role regional powers could also play in multilateral intuitions at regional and sub-regional levels. The current research, therefore, queries the role of regional hegemony in the employment of multilateral institutions in achieving foreign policy goals. It seeks to provide basic elements underlining the involvement of Nigeria in international organizations. As Nigeria conducts most of its external relations through multilateral diplomacy, it is imperative to provide a conceptual basis upon which such a role can be defined. In doing this we present the contemporary case study of Nigeria’s involvement in Mail to buttress our claim. The article relies on the theoretical precept of Regional Security Complex which emphasizes the role of state actors in the multilateral institutions to stem the tides of regional insecurity. In addition, the study uses newspapers, textbooks, speeches, archival records, articles in journals, and internet sources. In utilizing all these data sources, the use of latent content analysis and textual mining in interpreting and analyzing the data is upheld. Thus, the research found that Nigeria needs to be more proactive and assertive in Africa’s regional institutions in order to mitigate the insecurity issue in West Africa. The research, therefore, concludes that Nigeria, as the sole regional power in West Africa, needs to act fast to prevent the total collapse of security architecture in West Africa and the Sahel.